Dispersion, method for producing dispersion, and molded product

A dispersion of tetrafluoroethylene polymer powder and anisotropic fillers with low Mohs hardness addresses the issue of property deterioration in molded articles by ensuring stable dispersion and high physical properties through controlled mixing and orientation.

JP7616070B2Active Publication Date: 2025-01-17AGC INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021562707
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-15
Filing Date
2020-12-03
Publication Date
2025-01-17
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

The high melt viscosity of fluoropolymers like PFA and FEP requires strong stress during melt-kneading, leading to deterioration of the physical properties of anisotropic fillers, particularly those with low hardness, resulting in impaired properties in molded articles.

Method used

A dispersion containing tetrafluoroethylene polymer powder and anisotropic fillers with Mohs hardness of 4 or less, where the polymer powder has a smaller average particle diameter than the filler, and is mixed with a liquid dispersion medium, enhancing dispersibility and handling properties.

Benefits of technology

The dispersion achieves stable dispersion and molded products with high physical properties, including excellent electrical properties and improved mechanical strength, thermal conductivity, and orientation of the anisotropic filler.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616070000001
    Figure 0007616070000001
  • Figure 0007616070000002
    Figure 0007616070000002
Patent Text Reader

Abstract

[Problem] To provide a dispersion liquid containing a prescribed tetrafluoroethylene-based polymer and a prescribed anisotropic filler, a method for producing the dispersion liquid, and a molded article highly endowed with the physical properties of the two materials. [Solution] This dispersion liquid contains a powder of a tetrafluoroethylene-based polymer including units based on a perfluoro(alkylvinylether) and units based on hexafluoropropylene, an anisotropic filler having a Mohs hardness of 4 or lower, and a liquid dispersion medium. The average particle size of the powder is smaller than the average particle size of the anisotropic filler. This molded article contains a prescribed tetrafluoroethylene-based polymer including units based on a perfluoro(alkylvinylether), and the anisotropic filler. The proportion of the anisotropic filler in the molded article is 10 mass% or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dispersion containing a specific anisotropic filler, a method for producing the same, and a molded product. [Background technology]

[0002] Heat-meltable fluoropolymers such as tetrafluoroethylene polymers (PFA) containing units based on perfluoro(alkyl vinyl ether) and tetrafluoroethylene polymers (FEP) containing units based on hexafluoropropylene have excellent physical properties such as mold releasability, electrical insulation, water and oil repellency, chemical resistance, weather resistance, and heat resistance, and are used after being processed into various molded articles. Patent Document 1 describes an electric wire tube with excellent electrical insulation properties, which is obtained by melt-kneading a dry blend of PFA powder and boron nitride filler, and extrusion molding the mixture. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-224228 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the melt viscosity of such fluoropolymers is generally high, and strong stress is required when melt-kneading the fluoropolymers and the filler. In this case, the properties that the filler originally has (particularly, physical properties such as shape and surface condition) are damaged, and the physical properties of the filler in the molded product tend to decrease. The present inventors have found that this tendency is prominent in the case of a brittle filler with low hardness, particularly in the case of a low-hardness and anisotropic filler. The present inventors have conducted extensive research to obtain a material suitable for molding such a molded product without relying on melt kneading. As a result, they have found that a dispersion containing a powder of a specific fluoropolymer and a specific anisotropic filler has excellent dispersion stability and excellent handling properties such as coatability. Furthermore, they have found that a molded product formed from the dispersion is unlikely to lose the inherent properties of the anisotropic filler and has the physical properties of both of them at a high level. It is an object of the present invention to provide such dispersions and moldings. [Means for solving the problem]

[0005] The present invention has the following aspects. [1] A dispersion comprising a powder of a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether) or units based on hexafluoropropylene, an anisotropic filler having a Mohs hardness of 4 or less, and a liquid dispersion medium, wherein the average particle size of the powder is smaller than the average particle size of the anisotropic filler. [2] The dispersion liquid of [1], wherein the content of the tetrafluoroethylene-based polymer and the content of the anisotropic filler are each 5% by mass or more. [3] The dispersion of [1] or [2], wherein the anisotropic filler has a scale-like or plate-like shape. [4] The dispersion liquid according to any one of [1] to [3], wherein the anisotropic filler has an aspect ratio of 2 or more. [5] The dispersion according to any one of [1] to [4], wherein the anisotropic filler is an anisotropic filler containing boron nitride or talc. [6] The dispersion of any one of [1] to [5], further comprising a polytetrafluoroethylene powder or an aromatic polymer. [7] Any of the dispersions [1] to [6], in which the component dispersion layer rate is 60% or more. [8] A method for producing the dispersion liquid according to any one of [1] to [7], comprising mixing the powder, the anisotropic filler, an inorganic filler having an average particle diameter smaller than that of the anisotropic filler, and a liquid dispersion medium. [9] The manufacturing method according to [8], wherein the mixing is carried out by stirring.

[10] A molded article comprising a tetrafluoroethylene-based polymer containing units based on perfluoro(alkyl vinyl ether) and an anisotropic filler having a Mohs hardness of 4 or less, The tetrafluoroethylene-based polymer is a polymer having a polar functional group, or a polymer containing 2.0 to 5.0 mol % of units based on the perfluoro(alkyl vinyl ether) relative to all units and having no polar functional group, and the proportion of the anisotropic filler in the molded product is 10 mass % or more.

[11] The molded article according to

[10] , wherein the aspect ratio of the anisotropic filler is 2 or more.

[12] The molded product according to

[11] , wherein the anisotropic filler is a scaly anisotropic filler containing boron nitride or a plate-like anisotropic filler containing talc.

[13] The molded product according to any one of

[10] to

[12] , wherein the anisotropic filler has an average particle size of 1 μm or more.

[14] The molded article according to any one of

[10] to

[13] , further comprising polytetrafluoroethylene or an aromatic polymer.

[15] The molded product according to any one of

[10] to

[14] , which is a layered molded product having a thickness of 150 μm or less. Effect of the Invention

[0006] According to the present invention, a dispersion containing a powder of a specific fluoropolymer and a specific anisotropic filler and having excellent dispersibility and handleability can be obtained. In addition, a molded product having high physical properties of both the powder and the anisotropic filler and having particularly excellent electrical properties can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The following terms have the following meanings. "Average particle size (D50)" is the cumulative 50% volumetric diameter of a target object (powder or filler) determined by laser diffraction / scattering. In other words, the particle size distribution of the target object is measured by laser diffraction / scattering, the total volume of the target particle group is set as 100%, and a cumulative curve is calculated. The average particle size (D50) is the particle size at the point on the cumulative curve where the cumulative volume is 50%. "D90" is the volume-based cumulative 90% diameter of an object, measured in a similar manner. The "particle size distribution" is a distribution shown by a curve plotting the particle amount (%) in each particle size interval determined in the same manner. "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). The "glass transition point" is a value measured by analyzing a polymer using a dynamic mechanical analysis (DMA) method. The "unit" in a polymer may be an atomic group formed directly from a monomer by a polymerization reaction, or may be an atomic group in which a part of the structure is converted by treating a polymer obtained by a polymerization reaction with a predetermined method. A unit based on monomer A contained in a polymer is also simply referred to as a "monomer A unit".

[0008] The dispersion of the present invention (hereinafter also referred to as "the present dispersion") contains a powder (hereinafter also referred to as "F powder") of a tetrafluoroethylene-based polymer (hereinafter also referred to as "F polymer") containing units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) or units based on hexafluoropropylene (HFP) (HFP units), an anisotropic filler having a Mohs hardness of 4 or less, and a liquid dispersion medium. In addition, the average particle size of the F powder is smaller than the average particle size of the anisotropic filler. In this dispersion, the F powder and the anisotropic filler are dispersed. This dispersion has excellent dispersion stability and handling properties, and it is easy to form a molded product that has high physical properties of F polymer and anisotropic filler. The reason for this is not entirely clear, but it is thought to be as follows.

[0009] The anisotropic filler in the present invention can be said to be a fragile filler having an indefinite shape and various properties (crystal habits, etc.). In the present dispersion, the anisotropic filler is unstable and prone to aggregation or sedimentation. In addition, the shape or properties of the anisotropic filler are prone to being destroyed by physical stress (shear stress, etc.). On the other hand, F polymer is a polymer having plasticity typified by thermal melt processability, and its powder (F powder) is less susceptible to the effects of physical stress and has excellent dispersibility. The present dispersion contains the F powder in a state where the particle size is smaller than the average particle size of the anisotropic filler, in other words, densely, and the affinity between the anisotropic filler and the F powder is relatively likely to be increased. In other words, since the F powder is densely contained in the present dispersion in a finer form, it is considered that pseudo secondary particles are easily formed between the F powder and the anisotropic filler. As a result, the dispersion state of the anisotropic filler is stabilized, and the present dispersion is considered to be excellent in dispersion stability and handleability.

[0010] In addition, if the F powder is melted and sintered while removing the liquid dispersion medium from this dispersion, it is easy to mold a molded product while suppressing deformation of the anisotropic filler. In addition, during the process of removing the liquid dispersion medium, the anisotropic filler is oriented, and a molded product that is highly filled is easily obtained. As a result, it is believed that a molded product that highly combines the physical properties of the F polymer and the physical properties of the anisotropic filler was obtained from this dispersion. For example, when a molded product is formed from the present dispersion containing a scaly or plate-like anisotropic filler, the anisotropic filler is oriented parallel to the surface (plane direction) of the molded product, and the physical properties of the anisotropic filler in the molded product are easily expressed to a high degree. Therefore, when the present dispersion is used, the physical properties of the F polymer and the physical properties of the anisotropic filler are easily expressed to a high degree even in a thin-layer molded product.

[0011] Furthermore, if the anisotropic filler is scaly or plate-like, the anisotropic filler forms a card house structure, which not only improves the liquid properties (viscosity, dispersion stability, etc.) of the dispersion, but also makes it easier for the anisotropic filler to disperse to a higher degree in the molded product formed therefrom. As a result, the molded product is more likely to have excellent electrical properties. In addition, when the molded product is subjected to stress, the anisotropic filler is more likely to disperse the stress, making it easier to improve the mechanical strength (bending property, etc.). Furthermore, since paths for the anisotropic filler are formed in the molded product, the thermal conductivity of the molded product is more likely to be improved.

[0012] The F powder in the present dispersion preferably comprises an F polymer. The content of the F polymer in the powder is preferably 80% by mass or more, more preferably 100% by mass. Other components that may be included in the F powder include resins or inorganic substances different from the F polymer. The different resins include aromatic polyesters, polyamideimides, thermoplastic polyimides, polyphenylene ethers, and polyphenylene oxides. Examples of inorganic substances include silicon oxide (silica), metal oxides (beryllium oxide, cerium oxide, alumina, soda alumina, magnesium oxide, zinc oxide, titanium oxide, etc.), boron nitride, and magnesium metasilicate (steatite).

[0013] F powder containing a resin or inorganic substance different from an F polymer preferably has a core-shell structure having an F polymer as a core and the above-mentioned resin or inorganic substance as a shell, or has a core-shell structure having the above-mentioned resin or inorganic substance as a core and the F polymer as a shell. Such F powder is obtained, for example, by coalescence (collision, aggregation, etc.) of an F polymer powder and a powder of the above-mentioned resin or inorganic substance.

[0014] The D50 of the F powder is preferably 10 μm or less, more preferably 6 μm or less, and even more preferably 4 μm or less. The D50 of the F powder is preferably 0.01 μm or more, more preferably 0.1 μm or more, and even more preferably 1 μm or more. The D90 of the F powder is preferably 20 μm or less, and more preferably 10 μm or less. If the D50 and D90 of the F powder are within the above ranges, the affinity with the anisotropic filler is further improved, and the dispersion stability of the present dispersion and the physical properties of the molded product are more likely to be improved.

[0015] The content of the F powder in the present dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 25% by mass or more. The content of the F powder is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. If the content of the F powder is within this range, the affinity between the F powder and the anisotropic filler is increased due to the densely contained F powder, and the dispersion stability of the present dispersion is likely to be improved. In addition, the physical properties of the F polymer in the molded product are likely to be significantly expressed.

[0016] The F polymer in the present dispersion is a polymer containing units based on tetrafluoroethylene (TFE) (TFE units). The F polymer may contain both PAVE units and HFP units, or may contain only one of them. Preferably, PAVE is CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (PPVE), more preferably PPVE. The melting temperature of the F polymer is preferably from 280 to 325°C, more preferably from 285 to 320°C. The glass transition point of the F polymer is preferably from 75 to 125°C, more preferably from 80 to 100°C.

[0017] The F polymer may have a polar functional group (oxygen-containing polar group). The polar functional group may be contained in a unit in the F polymer, or may be contained in a terminal group of the main chain of the polymer. Examples of the latter embodiment include an F polymer having a polar functional group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer having a polar functional group obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment. The polar functional group is preferably a hydroxyl group-containing group or a carbonyl group-containing group, and from the viewpoint of the dispersion stability of the present dispersion, a carbonyl group-containing group is more preferable. The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is a group containing a carbonyl group (>C(O)), and is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.) or a carbonate group (-OC(O)O-). The number of carbonyl-containing groups in the F polymer is 1 × 10 6 The number of carbonyl-containing groups per unit is preferably 10 to 5000, more preferably 100 to 3000, and further preferably 800 to 1500. The number of carbonyl-containing groups in the F polymer can be quantified by the composition of the polymer or the method described in WO2020 / 145133.

[0018] The F polymer is preferably a tetrafluoroethylene-based polymer containing PAVE units and containing 1.5 to 5.0 mol % of PAVE units based on all units, and more preferably a polymer (1) containing PAVE units and units based on a monomer having a polar functional group and having a polar functional group, or a polymer (2) containing PAVE units and containing 2.0 to 5.0 mol % of PAVE units based on all units but not having a polar functional group. These F polymers not only have excellent dispersion stability in powder form, but also tend to distribute more densely and homogeneously in the molded product (polymer layer, etc.) formed from the dispersion. Furthermore, they tend to form microspherulites in the molded product, which tends to increase adhesion with other components. As a result, molded products that have high physical properties of each of the three components can be more easily obtained.

[0019] The polymer (1) preferably contains, based on all units, 90 to 98 mol % of TFE units, 1.5 to 9.97 mol % of PAVE units, and 0.01 to 3 mol % of units based on a monomer having a polar functional group. Moreover, the monomer having a polar functional group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (also called himic anhydride; hereinafter, also referred to as "NAH"). Specific examples of polymer (1) include the polymers described in WO 2018 / 16644.

[0020] The polymer (2) is composed only of TFE units and PAVE units, and preferably contains 95.0 to 98.0 mol % of TFE units and 2.0 to 5.0 mol % of PAVE units based on all units. The content of PAVE units in the polymer (2) is preferably 2.1 mol % or more, more preferably 2.2 mol % or more, based on all units. In addition, the polymer (2) having no polar functional group means that the number of carbon atoms constituting the polymer main chain is 1×10 6 This means that the number of polar functional groups in the polymer is less than 500 per unit. The number of the polar functional groups is preferably 100 or less, more preferably less than 50. The lower limit of the number of the polar functional groups is usually 0. The polymer (2) may be produced by using a polymerization initiator or a chain transfer agent that does not generate a polar functional group as a terminal group of the polymer chain, or by fluorinating an F polymer having a polar functional group (such as an F polymer having a polar functional group derived from a polymerization initiator at the terminal group of the main chain of the polymer). As a method of fluorination treatment, a method using fluorine gas (see JP 2019-194314 A, etc.) can be mentioned.

[0021] The Mohs hardness of the anisotropic filler in the present invention is 4 or less, and preferably 3 or less. The Mohs hardness of the anisotropic filler is preferably 1 or more, and more preferably 2 or more. Even if the anisotropic filler is brittle and has a Mohs hardness in this range, the present dispersion has excellent dispersion stability due to the affinity between the anisotropic filler and the F powder, and the physical properties of the filler in the molded product are likely to be improved. One type of anisotropic filler may be used, or two or more types having different average particle sizes or different types may be used.

[0022] The shape of the anisotropic filler in the present invention may be any of granular, needle-like (fibrous) and plate-like.Specific shapes of the anisotropic filler include spherical, scale-like, layered, leaf-like, apricot kernel-like, columnar, cockscomb-like, equiaxial, leaf-like, mica-like, block-like, flat, wedge-like, rosette-like, net-like and prismatic shapes. The anisotropic filler is preferably scaly or plate-like in shape. If a scaly or plate-like anisotropic filler is used, it forms a card house structure, which not only improves the liquid properties (viscosity, dispersion stability, etc.) of the dispersion, but also improves the orientation of the filler in the molded product, and easily enhances its functions (mechanical strength, thermal conductivity, electrical properties, etc.).

[0023] Examples of the anisotropic filler include carbon fillers, nitride fillers, mica fillers, clay fillers, and talc fillers. Fillers containing boron nitride or talc are preferred, and fillers containing boron nitride are more preferred. The crystal form of boron nitride may be any of hexagonal, rhombohedral, cubic, and wurtzite. The present dispersion containing such anisotropic fillers is excellent in dispersion stability and handleability. In addition, the electrical interference that the filler gives to the F polymer in the molded product is likely to increase, and as a result, the electrical properties (particularly, the dielectric loss tangent) of the molded product are likely to be good. In addition, the thermal conductivity of the molded product is likely to be good.

[0024] The boron nitride content in the filler containing boron nitride is preferably 95% by mass or more, more preferably 99% by mass or more, and even more preferably 99.5% by mass or more. The upper limit of the content is 100% by mass. In this case, the molded product tends to have low linear expansion properties and excellent electrical properties. When the anisotropic filler is added to water, the pH of the water may be acidic, neutral or alkaline, and is preferably alkaline. The specific surface area of ​​the anisotropic filler is 1 to 20 m 2 / g is preferable, and 3 to 8m 2 / g is more preferable. In this case, the anisotropic filler becomes more easily wetted in the dispersion liquid, and the affinity with the F powder is easily enhanced. In addition, in the molded product, the anisotropic filler and the F polymer are more uniformly dispersed (distributed), and the physical properties of both are easily expressed in a well-balanced manner.

[0025] The surface of the anisotropic filler may be surface-treated. Examples of surface treatment agents include polyhydric alcohols (trimethylolethane, pentaerythritol, propylene glycol, etc.), saturated fatty acids (stearic acid, lauric acid, etc.), esters thereof, alkanolamines, amines (trimethylamine, triethylamine, etc.), paraffin wax, silane coupling agents, silicones, polysiloxanes, and inorganic substances (oxides, hydroxides, hydrated oxides, or phosphates of aluminum, silicon, zirconium, tin, titanium, antimony, etc.). The surface treatment agent is preferably a silane coupling agent. In this case, the anisotropic filler and the F polymer powder have a higher affinity, and the dispersion stability of the dispersion liquid is easily improved. The silane coupling agent preferably has an amino group, a thiol group, a vinyl group, an acroyloxy group, or a methacryloyloxy group.

[0026] The anisotropic filler may be an anisotropic filler having a hydrophobic portion and a hydrophilic portion. Examples of such anisotropic fillers include an anisotropic filler having a hydrophobic layer on the surface and a hydrophilic layer inside. A specific example of such an anisotropic filler is a plate-shaped multi-layer filler having a hydrophobic layer, a hydrophilic layer (water-containing layer), and a hydrophobic layer in this order. The water content of the hydrophilic layer is preferably 0.3% by mass or more. In this case, not only is the dispersion state of the anisotropic filler in the dispersion liquid easily stable, but the orientation of the anisotropic filler is further enhanced when a molded product is molded from the dispersion liquid, and a molded product having a high degree of the physical properties of the F polymer and the physical properties of the anisotropic filler is easily obtained.

[0027] The D50 of the anisotropic filler is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more. The D50 of the anisotropic filler is preferably 25 μm or less, more preferably 20 μm or less. The D90 of the anisotropic filler is preferably 10 μm or more, more preferably 15 μm or more. The D90 of the anisotropic filler is preferably 30 μm or less, more preferably 20 μm or less. If the D50 and D90 of the anisotropic filler are within the above ranges, the affinity with the F powder is further improved, and the dispersion stability of the present dispersion and the physical properties of the molded product are more likely to be improved. Specific examples of such anisotropic fillers include scaly boron nitride filler and plate-like talc filler.

[0028] The aspect ratio of the anisotropic filler is preferably 2 or more, more preferably 3 or more, even more preferably 5 or more, and particularly preferably 10 or more. The aspect ratio of the anisotropic filler is preferably 10,000 or less. In this case, it is easy to improve the orientation of the filler in the molded product, and it is easy to enhance its function. Specifically, not only is the dispersion state of the anisotropic filler in the dispersion easy to stabilize, but the orientation of the anisotropic filler when molding a molded product from the dispersion is also further improved, and it is easy to obtain a molded product that has a high level of the physical properties of the F polymer and the physical properties of the anisotropic filler.

[0029] The aspect ratio of the anisotropic filler is a value obtained by dividing the average particle size (D50) of the anisotropic filler by the average minor axis (average length in the short direction) of the anisotropic filler. A specific example of such an anisotropic filler is a filler having an average minor axis of 1 μm or less, or an average major axis (average value of the length in the longitudinal direction) of 1 μm or more. A specific example of such an anisotropic filler is a plate-shaped talc filler. The anisotropic filler may have a single layer structure or a multi-layer structure, and an example of such an anisotropic filler is a talc filler having a three-layer structure.

[0030] Suitable specific examples of anisotropic fillers include boron nitride fillers (such as the "UHP" series manufactured by Showa Denko KK, the "HGP" series and "GP" series manufactured by Denka), and talc fillers (such as the "SG" series manufactured by Nippon Talc Co., Ltd.).

[0031] In this dispersion, the D50 of the F powder is smaller than that of the anisotropic filler. In other words, the dispersion contains fine F powder densely, which increases the affinity between the F powder and the anisotropic filler and improves the dispersion stability of the dispersion. Furthermore, the anisotropic filler is more uniformly dispersed in the molded product, making it easier for its physical properties to be significantly expressed. Specifically, it is preferable that the D50 of the F powder is 0.1 μm or more and less than 5 μm, and the D50 of the anisotropic filler is 1 μm or more and 25 μm or less.

[0032] A preferred embodiment of the filler contained in the present dispersion includes an anisotropic filler (hereinafter also referred to as "anisotropic filler 1") and an inorganic filler (hereinafter also referred to as "different filler") having a smaller average particle size than the anisotropic filler 1. In this case, the improvement in the dispersion stability of the present dispersion due to the interaction between the fillers and the ability of the different filler to form a dense molded product are balanced, and the physical properties (water resistance, low linear expansion, electrical properties, etc.) of the obtained molded product are more likely to be improved. The different filler may be an inorganic filler having an average particle size smaller than the anisotropic filler 1, and the material may be the same as or different from the anisotropic filler 1.

[0033] In this preferred embodiment, the average particle size of the anisotropic filler 1 is preferably more than 6 μm and 15 μm or less, and the average particle size of the different filler is preferably 1 μm or more and 6 μm or less. In this case, the anisotropic filler 1 is preferably a filler containing boron nitride, and the different filler is preferably a filler containing boron nitride or a magnesium metasilicate filler (steatite filler). In addition, the aspect ratio of the anisotropic filler 1 is preferably 10 or more, and the aspect ratio of the different filler is preferably 40 or less, more preferably less than 10. In this case, in the obtained molded product, the different fillers promote random orientation of the anisotropic filler 1, and the filler properties and the molded product properties (adhesiveness, rigidity, etc.) are easily balanced.

[0034] In this preferred embodiment, it is also preferred that the average particle size of the anisotropic filler 1 is more than 1 μm and not more than 15 μm, and the average particle size of the different filler is 0.01 μm or more and less than 1 μm. In this case, it is preferred that the anisotropic filler 1 is a filler containing boron nitride, and the different filler is a filler containing silicon oxide. The filler containing silicon oxide is preferably a silica filler or a magnesium metasilicate filler (steatite filler), and the surface of the filler containing silicon oxide is preferably treated with a silane coupling agent.

[0035] The filler containing silicon oxide is preferably substantially spherical. In this case, dense moldings are easily formed. The term "substantially spherical" means that the ratio of spherical particles having a minor axis to major axis ratio of 0.7 or more when observed with a scanning electron microscope (SEM) is 95% or more. Specific examples of such fillers containing silicon oxide include nearly spherical silica fillers (such as the "Admafine" series manufactured by Admatechs), spherical fused silica (such as the "SFP" series manufactured by Denka), hollow silica fillers (such as the "E-SPHERES" series manufactured by Taiheiyo Cement Corporation, the "Silinax" series manufactured by Nippon Steel Mining Co., Ltd., and the "Ecocospher" series manufactured by Emerson & Cumming Co., Ltd.), and steatite fillers (such as the "BST" series manufactured by Nippon Talc Co., Ltd.).

[0036] In this preferred embodiment, the different fillers promote random orientation of the anisotropic filler 1 in the molded product, and the filler properties in the molded product and the molded product properties (adhesiveness, surface smoothness, rigidity, etc.) are easily balanced. In other words, the orientation of the anisotropic filler 1 is partially disordered in the molded product, and the molded product is likely to have high electrical properties and low linear expansion resulting from high filler orientation, and high rigidity, adhesiveness, and surface smoothness resulting from the disorder of the filler orientation.

[0037] In addition, the filler in this preferred embodiment may be contained in a state having a multimodal particle size distribution. In this case, from the viewpoint of facilitating the formation of a dense molded product, it is preferable that the peak in the particle size distribution caused by the filler 1 is the highest. Specifically, it is preferable that the filler is contained in a state having a bimodal particle size distribution having peaks in the region of 6 μm or less and the region of over 6 μm.

[0038] In addition, in this preferred embodiment, at least a part of the filler may be attached to the surface of the F powder, or at least a part of the F powder may be attached to the surface. In this case, the dispersion liquid can be said to contain a composite of the F powder and the anisotropic filler 1, and the dispersion stability is further improved, and the physical properties (water resistance, low linear expansion, electrical properties, etc.) of the molded product formed therefrom are likely to be further improved.

[0039] Furthermore, in this preferred embodiment, the mass ratio of the content of the different filler to the content of the anisotropic filler 1 is preferably 0.1 or more, more preferably 0.2 or more. Moreover, the mass ratio is preferably 2 or less, more preferably 1 or less. In this case, the dispersion stability of the dispersion and the physical properties of the molded product are easily balanced.

[0040] The content of the anisotropic filler in the dispersion is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 25% by mass or more. The content of the F powder is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. In the present dispersion, the content of the F polymer and the content of the anisotropic filler are each preferably 5% by mass or more. The sum of the contents of both is preferably 60% by mass or less. Even if the F polymer and the anisotropic filler are contained at such a high ratio (content), as explained by the above-mentioned mechanism of action, the present dispersion has excellent dispersion stability, and it is easy to form a molded product having high physical properties of both.

[0041] From the viewpoint of improving dispersion stability and handling properties, the present dispersion preferably further contains a surfactant. The surfactant is preferably nonionic. The hydrophilic site of the surfactant preferably has an oxyalkylene group or an alcoholic hydroxyl group. The oxyalkylene group may be composed of one type or two or more types. In the latter case, the different types of oxyalkylene groups may be arranged randomly or in a block form. The oxyalkylene group is preferably an oxyethylene group.

[0042] The hydrophobic portion of the surfactant preferably has an acetylene group, a polysiloxane group, a perfluoroalkyl group, or a perfluoroalkenyl group. In other words, the surfactant is preferably an acetylene-based surfactant, a silicone-based surfactant, or a fluorine-based surfactant, and more preferably a silicone-based surfactant. As the fluorosurfactant, a fluorosurfactant having a hydroxyl group (particularly an alcoholic hydroxyl group) or an oxyalkylene group and a perfluoroalkyl group or a perfluoroalkenyl group is more preferable. Specific examples of surfactants include the "Ftergent" series (manufactured by Neos), the "Surflon" series (manufactured by AGC Seimi Chemical Co., Ltd.), the "Megafac" series (manufactured by DIC Corporation), the "Unidyne" series (manufactured by Daikin Industries, Ltd.), "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (manufactured by BYK Japan KK), and "KF-6011" and "KF-6043" (manufactured by Shin-Etsu Chemical Co., Ltd.). The content of the surfactant in the present dispersion is preferably 1 to 15% by mass, in which case the affinity between the components is enhanced, and the dispersion stability of the present dispersion is more likely to be improved.

[0043] The liquid dispersion medium in the present invention is a liquid compound that functions as a dispersion medium for the F powder and the anisotropic filler and is inactive at 25°C. The liquid dispersion medium may be water or a non-aqueous dispersion medium. The liquid dispersion medium may be one type or two or more types. In this case, it is preferable that the different liquid compounds are compatible with each other. The boiling point of the liquid dispersion medium is preferably 125 to 250° C. In this case, when a molded article is formed from the dispersion, the anisotropic filler is likely to be oriented, and the physical properties of the molded article are likely to be improved. From the viewpoint of dispersion stability of the present dispersion, the liquid dispersion medium is preferably one or more liquid compounds selected from the group consisting of amides, ketones and esters, and more preferably N-methyl-2-pyrrolidone, γ-butyrolactone, cyclohexanone or cyclopentanone. The content of the liquid dispersion medium in the present dispersion is preferably 50% by mass or more, more preferably 60% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less.

[0044] The viscosity of the present dispersion is preferably 50 mPa·s or more, more preferably 100 mPa·s or more. The viscosity of the present dispersion is preferably 10,000 mPa·s or less, more preferably 1,000 mPa·s or less, and even more preferably 800 mPa·s or less. The thixotropy ratio of the present dispersion is preferably 1.0 or more, more preferably 3.0 or less, and even more preferably 2.0 or less. The component dispersion layer ratio of the present dispersion is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. Here, the component dispersion layer ratio is a value calculated by the following formula from the total height of the present dispersion in the screw tube and the height of the component dispersion layer before and after standing when the present dispersion (18 mL) is placed in a screw tube (internal volume: 30 mL) and left at rest at 25° C. for 14 days. Component dispersion layer rate (%) = (component dispersion layer height) / (total height of this dispersion liquid) × 100 If no component-dispersed layer is observed after standing and there is no change in state, it is assumed that there is no change in the overall height of the dispersion liquid, and the component-dispersed layer rate is taken as 100%. Due to the above-mentioned mechanism of action, the present dispersion liquid is easy to adjust to the above-mentioned ranges of viscosity, thixotropy, and component dispersion layer ratio, and has excellent handleability.

[0045] The dispersion may further contain another resin (polymer) different from the F polymer. The other resin may be a thermosetting resin or a thermoplastic resin. Examples of other resins include epoxy resins, maleimide resins, urethane resins, elastomers, polyimides, polyamic acids, polyamideimides, polyphenylene ethers, polyphenylene oxides, liquid crystal polyesters, and fluoropolymers other than F polymers. A suitable embodiment of the other resin is a varnish of an aromatic polymer. The aromatic polymer is preferably an aromatic polyimide or an aromatic polyamic acid, more preferably a thermoplastic aromatic polyimide. In this case, the physical properties of the F polymer and the anisotropic filler are likely to be significantly expressed in the molded product. In addition, when forming a molded product from this dispersion, the powder fall of the F powder is also suppressed, and the adhesiveness is likely to be improved.

[0046] The content of the aromatic polymer in the present dispersion is preferably 1 to 30% by mass, more preferably 5 to 25% by mass. The ratio by mass of the content of the aromatic polymer to the content of the F polymer is preferably 1.0 or less, more preferably 0.1 to 0.7. A suitable embodiment of the other resin is a powder of polytetrafluoroethylene (PTFE). In this case, the physical properties based on PTFE (electrical properties such as low dielectric tangent) tend to be significantly exhibited in the molded product. In addition, PTFE acts as a nucleating agent, which makes it easier for the F polymer in the molded product to form fine crystals, improving the adhesion to the surface of the molded product and increasing its adhesiveness. In addition, it tends to improve the orientation of the filler in the molded product, which tends to increase its function.

[0047] The PTFE is preferably a PTFE having a number average molecular weight (Mn) of 200,000 or less, calculated based on the following formula (1) (low molecular weight PTFE). Mn = 2.1 × 10 10 ×ΔHc -5.16 ... (1) In formula (1), ΔHc represents the heat of crystallization (cal / g) of PTFE measured by differential scanning calorimetry. The Mn of the low molecular weight PTFE is preferably 100,000 or less, more preferably 50,000 or less. The Mn of the low molecular weight PTFE is preferably 10,000 or more.

[0048] The PTFE content in the present dispersion is preferably 1 to 30% by mass, more preferably 5 to 20% by mass. The mass ratio of the PTFE content to the F polymer content is preferably 1.0 or less, more preferably 0.1 to 0.4. When the present dispersion contains another resin, it may be produced by mixing the present dispersion with a powder of the other resin, or it may be produced by mixing the present dispersion with a varnish containing the other resin.

[0049] In addition to the above-mentioned components, the present dispersion may contain additives such as a thixotropic agent, an antifoaming agent, a silane coupling agent, a dehydrating agent, a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a brightening agent, a colorant, a conductive agent, a release agent, a surface treatment agent, a viscosity adjusting agent, a flame retardant, and an isotropic filler.

[0050] This dispersion can be produced by mixing F powder, anisotropic filler, and a liquid dispersion medium, and it is preferable to prepare a liquid composition containing F powder and a liquid composition containing anisotropic filler separately and mix the two to produce the dispersion. A specific method for producing the dispersion liquid includes mixing F powder, anisotropic filler 1, a different filler, and a liquid dispersion medium. In this mixing, the F powder and the liquid dispersion medium may be mixed in advance to form a liquid composition, or the anisotropic filler 1 and the different filler may be mixed in advance.

[0051] Examples of the mixer used for mixing include a mixer with an agitating blade, a Henschel mixer, a ribbon blender, a rocking mixer, a vibration mixer, a rotary mixer, and the like. Specific examples include a homodisper, a homogenizer, and a ball mill. The mixing method may be either batch or continuous. The mixer used for batch mixing is preferably a Henschel mixer, a pressure kneader, a Banbury mixer or a planetary mixer.

[0052] The mixing is preferably carried out by stirring, more preferably by rotary stirring with a stirring blade. The stirring speed is preferably 800 rpm or more, more preferably 2000 rpm or more. The stirring speed is preferably 10000 rpm or less, more preferably 8000 rpm or less. In this case, shear is applied to the F powder and the anisotropic filler, which makes it easy to disintegrate aggregates, and it is easy to obtain the present dispersion liquid with excellent dispersibility. Furthermore, if the anisotropic filler is scaly or plate-like, the layered agglomerates (secondary particles) of the anisotropic filler that are formed are usually efficiently disintegrated while forming a house-of-cards structure, making it easier to form a dispersion liquid with excellent dispersibility.

[0053] The molded article of the present invention (hereinafter also referred to as "the molded article") contains a tetrafluoroethylene-based polymer containing PAVE units (hereinafter also referred to as "PFA-based polymer") and an anisotropic filler having a Mohs hardness of 4 or less. The PFA-based polymer is a polymer having a polar functional group, or a polymer containing 2.0 to 5.0 mol % of PAVE units relative to all units and having no polar functional group, and the proportion (content) of the anisotropic filler in the molded article is 10 mass % or more. The shape of the molded product may be layered, plate-like, or block-like, with layered being preferred. The thickness of the layered molded product is preferably 150 μm or less. Such layered molded products are useful for producing impregnated products such as films and prepregs, laminates, etc.

[0054] The definition and scope of the anisotropic filler in the present molded article, including preferred embodiments, are the same as those of the anisotropic filler in the present dispersion. The types and ranges of polar functional groups possessed by the PFA-based polymer in the present molded article, including preferred embodiments, are the same as those in the F polymer. The PFA-based polymer is preferably polymer (1) or polymer (2).

[0055] The content of the anisotropic filler in the present molded product is preferably 15% by mass or more, more preferably 25% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less. The content of the PFA-based polymer in the molded product is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more. The content of the PFA-based polymer is preferably 95% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less. When the content of the PFA-based polymer is within this range, the physical properties of the PFA-based polymer are easily manifested in the molded product. In addition, the powder falling off of the anisotropic filler from the molded product is suppressed.

[0056] The molded article further preferably contains an aromatic polymer (particularly, an aromatic polyimide) or PTFE. The definitions and ranges of the aromatic polymer and PTFE in the molded article and the mass ratio of the content of each to the content of the F polymer are the same as those in the dispersion. The present molded product is preferably formed from the present dispersion. Specifically, by applying the present dispersion to the surface of a substrate and removing the liquid dispersion medium, a layer containing a PFA-based polymer and anisotropic filler (hereinafter also referred to as the present layer) can be easily formed on the surface of the substrate as the present molded product. More specifically, by applying the present dispersion to the surface of a substrate, heating the substrate to remove the liquid dispersion medium, and further heating to melt and sinter the PFA-based polymer, a laminate having the substrate and the present layer formed on the surface of the substrate can be obtained. The temperature for the former heating is preferably 120°C to 200°C. Meanwhile, the temperature for the latter heating is preferably 250°C to 400°C, more preferably 300°C to 380°C.

[0057] Examples of the substrate include metal substrates (metal foils of copper, nickel, aluminum, titanium, alloys thereof, etc.), resin films (films of polyimide, polyarylate, polysulfone, polyarylsulfone, polyamide, polyetheramide, polyphenylene sulfide, polyaryletherketone, polyamideimide, liquid crystalline polyester, liquid crystalline polyesteramide, etc.), and prepregs (precursors of fiber-reinforced resin substrates). The dispersion is preferably applied by coating, and examples of the coating method include spraying, roll coating, spin coating, gravure coating, microgravure coating, gravure offset, knife coating, kiss coating, bar coating, die coating, fountain-meyer bar, and slot die coating. Examples of the heating method include a method using an oven, a method using a ventilated drying furnace, and a method using heat rays such as infrared rays.

[0058] The thickness of this layer is preferably 0.1 to 150 μm. Specifically, if the substrate is a metal foil, the thickness of this layer is preferably 1 to 30 μm. If the substrate is a resin film, the thickness of this layer is preferably 1 to 150 μm, and more preferably 10 to 50 μm. The present dispersion may be applied to only one surface of the substrate, or may be applied to both surfaces of the substrate. In the former case, a laminate having the substrate and the present layer on one surface of the substrate is obtained, and in the latter case, a laminate having the substrate and the present layer on both surfaces of the substrate is obtained. The latter laminate is less likely to warp, and therefore has excellent handling properties during processing. Specific examples of such laminates include metal clad laminates having a metal foil and this layer on at least one surface of the metal foil, and multilayer films having a polyimide film and this layer on both surfaces of the polyimide film. These laminates have excellent physical properties such as electrical properties, and are suitable as materials for printed circuit boards, etc. Specifically, such laminates can be used in the manufacture of flexible printed circuit boards and rigid printed circuit boards. EXAMPLES

[0059] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [powder] Powder 1: Contains 97.9 mol% TFE units, 0.1 mol% NAH units, and 2.0 mol% PPVE units, in that order, and has a carbonyl group with a main chain carbon number of 1 × 10 6Powder (D50: 2.1 μm) made of PFA-based polymer 1 (melting temperature: 300°C) with 1000 particles per particle Powder 2: Contains 97.5 mol% TFE units and 2.5 mol% PPVE units, in that order, and has a carbonyl group with a main chain carbon number of 1 × 10 6 Powder (D50: 1.8 μm) made of PFA-based polymer 2 (melting temperature 305°C) with 40 particles per particle Powder 3: Powder made of PFA-based polymer 2 (D50: 5.3 μm) Powder 4: Powder made of PTFE with a number average molecular weight of 20,000 (D50: 3.2 μm)

[0060] [Anisotropic filler] Filler 1: A flake-like filler made of boron nitride (D50: 7.0 μm) Filler 2: Scaly filler made of boron nitride (D50: 3.7 μm) Filler 3: A flake-like filler made of boron nitride (D50: 7.3 μm) Filler 4: Plate-shaped talc filler having a three-layer structure having a hydrophobic layer, a hydrophilic layer, and a hydrophobic layer in that order (D50: 4.5 μm, average major axis: 5.1 μm, average minor axis: 0.2 μm, aspect ratio: 25, "SG-95" manufactured by Nippon Talc Co., Ltd.) The Mohs hardness of Fillers 1 to 3 is 2, and the Mohs hardness of Filler 4 is 1. Fillers 1, 2 and 4 are surface-treated with a silane coupling agent. [Liquid dispersion medium] NMP: N-methyl-2-pyrrolidone

[0061] [Surfactants] Surfactant 1: CH2=C(CH3)C(O)OCH2CH2(CF2)6F and CH2=C(CH3)C(O)(OCH2CH2) 23 A nonionic polymer that is a copolymer with OH and has a fluorine content of 35% by mass. [Aromatic polymer varnish] Varnish 1: Varnish in which thermoplastic aromatic polyimide (PI1) is dissolved in NMP (solid concentration: 18% by mass)

[0062] 2. Dispersion liquid production example (Example 1) First, powder 1, varnish 1, surfactant 1, and NMP were added to a pot, and zirconia balls were added. The pot was then rolled at 150 rpm for 1 hour to prepare a composition. Filler 1, surfactant 1, and NMP were added to another pot, and zirconia balls were added. The pot was then rolled at 150 rpm for 1 hour to prepare a composition. In addition, both compositions were placed in a separate pot, and zirconia balls were added. The pot was then rolled at 150 rpm for 1 hour to obtain Dispersion 1 (viscosity: 400 mPa s) containing Powder 1 (11 parts by mass), Filler 1 (11 parts by mass), PI 1 (7 parts by mass), Surfactant 1 (4 parts by mass), and NMP (67 parts by mass). (Examples 2 to 9) Dispersions 2 to 9 were obtained in the same manner as in Example 1, except that the types and amounts of the powder, filler, varnish, surfactant, and liquid dispersion medium were changed as shown in Table 1 below. (Example 10) Dispersion liquid 10 was obtained in the same manner as in Example 1, except that 3 parts by mass of Filler 1 and 8 parts by mass of Filler 2 were used instead of 11 parts by mass of Filler 1.

[0063] [Table 1]

[0064] 3. Manufacturing examples of molded products Dispersion liquid 1 was applied to the surface of a long copper foil (thickness 18 μm) using a bar coater to form a wet film. The metal foil on which the wet film was formed was then passed through a drying oven at 120° C. for 5 minutes and dried by heating to obtain a dry film. The dry film was then heated at 380° C. for 3 minutes in a nitrogen oven. This produced a laminate 1 having a metal foil and a polymer layer (thickness 5 μm) as a molded product containing a molten and fired product of powder 1 and filler 1 on its surface. Laminates 2 to 10 were produced in the same manner as laminate 1, except that dispersion 1 was changed to dispersions 2 to 10, respectively.

[0065] 4. Evaluation 4-1. Dispersion stability of dispersion liquid Dispersions 1 to 10 were stored in containers at 25° C., and then their dispersibility was visually confirmed and the dispersion stability was evaluated according to the following criteria. [Evaluation Criteria] ⊚: No aggregates were visible. ◯: Fine aggregates were visible on the side walls of the container. They were uniformly redispersed when lightly stirred. △: Aggregates are visible at the bottom of the container. They are uniformly redispersed when stirred with shear. ×: Aggregates are visible at the bottom of the container. Redispersion is difficult even with stirring under shear.

[0066] 4-2. Physical properties of laminates 4-2-1.Surface smoothness The surface smoothness of the polymer layers of the Laminates 1 to 9 was visually confirmed, and the surface smoothness was evaluated according to the following criteria. [Evaluation Criteria] ◯: The entire surface of the polymer layer is smooth. Δ: Irregularities due to missing polymer or filler are visible on the edge of the surface of the polymer layer. ×: Irregularities due to missing polymer or inorganic filler are visible over the entire surface of the polymer layer.

[0067] 4-2-2. Linear expansion coefficient For each of the laminates 1 to 4, 9, and 10, a square test piece measuring 180 mm on each side was cut out, and the linear expansion coefficient of the test piece was measured in the range of 25° C. or more and 260° C. or less according to the measurement method specified in JIS C 6471:1995. [Evaluation Criteria] ○: Less than 30 ppm / ℃. ×: More than 30 ppm / ℃.

[0068] 4-2-3.Dielectric tangent For each of the laminates 1 to 4, 9, and 10, the copper foil of the laminate was removed by etching with an aqueous ferric chloride solution to produce a single polymer layer, and the dielectric tangent of the polymer layer (measurement frequency: 10 GHz) was measured by the SPDR (split post dielectric resonance) method. [Evaluation Criteria] ◯: The dielectric tangent is less than 0.0010. △: The dielectric tangent is 0.0010 or more and 0.0025 or less. ×: The dielectric tangent is more than 0.0025. The evaluation results are summarized in Table 2 below.

[0069] [Table 2]

[0070] 5. Dispersion liquid production example (part 2) (Example 11) First, Powder 1, Surfactant 1, and NMP were added to a pot and mixed, and the mixture was stirred with a homodisper at 2000 rpm for 1 hour to prepare a composition. Filler 1, Surfactant 1, and NMP were added to another pot and the mixture was stirred with a homodisper at 2000 rpm for 1 hour to prepare a composition. Both compositions were added to another pot and stirred with a homodisper at 2000 rpm for 1 hour to obtain Dispersion 11 (viscosity: 300 mPa s, component dispersion layer ratio: 80%) containing Powder 1 (11 parts by mass), Filler 1 (11 parts by mass), Surfactant 1 (4 parts by mass), and NMP (74 parts by mass). (Example 12) Dispersion 12 was obtained in the same manner as in Example 11, except that an ultrasonic homogenizer without stirring by a stirring blade was used instead of the Homodisper (viscosity: 300 mPa·s, component dispersion layer ratio: 50%).

[0071] 6. Example of laminate manufacturing (part 2) The dispersion liquid 11 was applied to the surface of an aluminum foil having a thickness of 18 μm by a roll-to-roll gravure reverse method to form a liquid coating. Next, the aluminum foil on which the liquid coating was formed was passed through a drying oven at 120° C. for 5 minutes and dried by heating. After that, the dried coating was heated at 340° C. for 3 minutes in a far-infrared oven under a nitrogen atmosphere. This produced a laminate 11 in which a polymer layer (thickness: 10 μm) was formed on the surface of the aluminum foil. Furthermore, a laminate 12 was produced in the same manner as the laminate 11, except that the dispersion liquid 12 was used instead of the dispersion liquid 11. As a result of observing the cross section of each laminate by SEM, the distribution state of the filler 1 was denser in the polymer layer of the laminate 11 than in the polymer layer of the laminate 12. In addition, the polymer layer of the laminate 11 had a lower dielectric tangent than the polymer layer of the laminate 12. The laminate 11 was superior to the laminate 12 in thermal conductivity and bendability. [Industrial Applicability]

[0072] The dispersion of the present invention has excellent dispersion stability and can be used to produce molded products (films, impregnated products such as prepregs, laminates, coating materials, etc.) that have physical properties based on the F polymer (PFA-based polymer) and characteristics based on the anisotropic filler. The molded product of the present invention is useful as antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, paints, cosmetics, etc., and specifically, it is useful as an outer surface coating material for heat dissipation members, electric wire coating materials (aircraft electric wires, etc.), electrical insulating tapes, insulating tapes for oil drilling, materials for printed circuit boards, separation membranes (microfiltration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode binders (for lithium secondary batteries, for fuel cells, etc.), copy rolls, covers for furniture, automobile dashboards, home appliances, etc., sliding members (load bearings, sliding shafts, valves, bearings, gears, cams, belt conveyors, food transport belts, etc.), tools (shovels, files, saws, etc.), boilers, hoppers, pipes, ovens, baking molds, chutes, dies, toilets, container coating materials, and heat exchangers (fins, heat transfer tubes, etc.) for cold and hot equipment, etc.

Claims

1. A dispersion liquid comprising: a powder of a tetrafluoroethylene-based polymer containing a unit based on perfluoro(alkyl vinyl ether); an anisotropic filler containing boron nitride or talc having a Mohs hardness of 4 or less; and a liquid dispersion medium, wherein the powder has an average particle size of 0.01 μm or more and 10 μm or less, and the anisotropic filler has an average particle size of 1 μm or more and 25 μm or less, and the average particle size of the powder is smaller than the average particle size of the anisotropic filler.

2. The dispersion according to claim 1 , wherein the content of the tetrafluoroethylene-based polymer and the content of the anisotropic filler are each 5% by mass or more.

3. The dispersion according to claim 1 or 2, wherein the anisotropic filler has a scale-like or plate-like shape.

4. The dispersion according to any one of claims 1 to 3, wherein the anisotropic filler has an aspect ratio of 2 or more.

5. The dispersion according to any one of claims 1 to 4, further comprising a powder of polytetrafluoroethylene, an aromatic polyimide, or an aromatic polyamic acid.

6. The dispersion according to any one of claims 1 to 5, wherein the component dispersion layer rate is 60% or more.

Citation Information

Patent Citations

  • Fluoropolymer filled with conductor

    JP1994001902A

  • Atomizable powder of non-fibrillating fluoropolymer

    JP2002540275A

  • Composition, and method for producing foam molded material and electric wire

    JP2014224228A

  • Liquid composition, and method for manufacturing film and layered body using same

    WO2018016644A1